Odpowiedź :
Szczegółowe wyjaśnienie:
[tex]a)\ \sqrt[3]{8^3}=8\\\\b)\ \sqrt[3]8-2\sqrt[3]{27}=2-2\cdot3=2-6=-4\\\\c)\ \sqrt[3]1\cdot\sqrt[3]{-64}=1\cdot(-4)=-4\\\\d)\ 2\sqrt[3]{6^3}\cdot\sqrt[3]0=2\cdot6\cdot0=0\\\\e)\ 4\sqrt[3]{27}-\sqrt[3]{64}=4\cdot3-4=12-4=8\\\\f)\ \sqrt[3]{1000}-2\sqrt[3]{125}=100-2\cdot5=10-10=0[/tex]
Skorzystałem z:
[tex]\sqrt[3]{a}=b\iff b^3=a\\\\\sqrt[3]{a^3}=a[/tex]
[tex]zad.6\\\\a)~~\sqrt[3]{8^{3} } =8^{3\cdot \frac{1}{3} } =8\\\\b)~~\sqrt[3]{8} -2\sqrt[3]{27} =\sqrt[3]{2^{3} } -2\sqrt[3]{3^{3} }=2-2\cdot 3=2-6=-4\\\\c)~~\sqrt[3]{1} \cdot \sqrt[3]{-64} =\sqrt[3]{1^{3} } \cdot \sqrt[3]{(-4)^{3} } =1\cdot (-4)=-4\\\\d)~~2\sqrt[3]{6^{3} } \cdot \sqrt[3]{0} =2\cdot6 \cdot 0 = 0\\\\e)~~4\sqrt[3]{27} - \sqrt[3]{64}=4\sqrt[3]{3^{3} } -\sqrt[3]{4^{3} } =4\cdot 3 - 4=12-4=8\\\\d)~~\sqrt[3]{1000}-2\sqrt[3]{125} =\sqrt[3]{10^{3} } -2\sqrt[3]{5^{3} } =10-2\cdot 5=10-10=0[/tex]
korzystałam ze wzoru:
[tex]\sqrt[n]{x^{n} } =x^{n\cdot \frac{1}{n} } =x^{1} =x[/tex]